2018
DOI: 10.1515/jcim-2017-0183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foot reflexology and slow stroke back massage on the severity of fatigue in patients undergoing hemodialysis: A semi-experimental study

Abstract: Background Fatigue is one of the most disturbing and the most common symptoms reported by patients dialyzed. There are methods available on complementary and alternative medicine, through which nurses can help patients to promote their health. Reflexology is a treatment which has a long history and is considered as one of the most popular and the most widespread methods of alternative medicine. In this study, the effects of foot reflexology and slow stroke back massage on the severity of fatigue in patients tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
11

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 18 publications
0
16
0
11
Order By: Relevance
“…Reflexology can reduce fatigue, pain and cramps, and improve quality of sleep in patients undergoing hemodialysis [39]. Ahmadidarrehsima et al (2018) reported that reflexology was a quite safe intervention to reduce fatigue in patients undergoing hemodialysis [40].…”
Section: Discussionmentioning
confidence: 99%
“…Reflexology can reduce fatigue, pain and cramps, and improve quality of sleep in patients undergoing hemodialysis [39]. Ahmadidarrehsima et al (2018) reported that reflexology was a quite safe intervention to reduce fatigue in patients undergoing hemodialysis [40].…”
Section: Discussionmentioning
confidence: 99%
“…Among the 14 studies, six different measures were utilised to measure fatigue and three different measures to assess quality of life. The measurement of fatigue include Piper Fatigue Scale [17], Novel Fatigue Scale for Hemodialysis [18]; Fatigue Severity Scale [19][20][21], Fatigue Scale [22]; Rothen Fatigue Scale [23], and visual analog scale [24]. Quality of life were assessed using PROMIS [18,25,26] and KDQOL-SF 3 [19][20][21][22][23][24][27][28][29][30].…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Although fatigue and sleep are typically related problems, fatigue has been studied apart from sleep in at least a few studies. In one study, fatigue was studied in patients undergoing hemodialysis for which fatigue is one of the most disturbing symptoms (Ahmadidarrehsima, Mohammadpourhodki, Ebrahimi, Keramati & Dianatinasab, 2018). In this study, foot massage and slow stroke back massage were performed twice per week for three weeks.…”
Section: Physical Conditionsmentioning
confidence: 99%